Maintenance of quality of eggs submitted to treatment with propolis extract and sanitizers - Ana Cristina Baltazar Soares; Daniela Aguiar Penha Brito; Swenia Christina Pinheiro Soares; Karolynne Sousa Gomes; Gleycy Kelly Moraes Santos Saldanha; Vânia da Silva Soares (Acta Scientiarum. Animal Sciences, 2021)
This study aimed to evaluate the internal and microbiological quality of eggs submitted to different types of shell treatments. One hundred and forty-four fresh red eggs were distributed in a scheme of 4 treatments (no washing; washing and immersion in chlorine; washing and immersion in peracetic acid; and washing and spraying of propolis extract) x 5 storage periods (7, 14, 21, 28, and 35 days), stored at 25°C, in each period 6 eggs per treatment were analyzed. The parameters to assess were: weight loss; shell weight; yolk weight; albumen weight, yolk diameter; yolk height; albumen height and Haugh unit (HU). The microbiological quality of eggs was evaluated at 35 days through analysis for aerobic mesophilic bacteria, thermotolerant coliforms, Staphylococcus spp., Salmonella spp. and molds and yeasts. The treatment with propolis extract was the only effective one to maintain the high HU quality of the eggs until 21 days of storage at 25°C and was effective against microbiological contamination of all bacterial groups. The results presented showed greater effectiveness of the propolis extract for maintenance of internal and microbiological quality of eggs, it can be an alternative product to chemical sanitizers.